RELEVANSI KEHIDUPAN SEHARI-HARI DENGAN SENI PERTUNJUKAN TRADISIONAL - Jefrizal, Jefrizal (Jurnal Ilmu Budaya, 2017)
This writing deals with the relevance of daily life and traditional theatre performance, tonil. In this case, the traditional theatre performance focuses only on the existence and phenomena of Ogam in the life of Bengkalis’ people in which it is related to the people’a theatre performance. Ogam is a simple chat people utter in some conditions. The better the people chat, the more successful those people attract other attention. In certain situation, it is also found that someone doesn’t chat properly and it may cause uncomfortable chat and it may also stop the interesting chat. This ogam is signed by many coffee shops found in Bengkalis in which people usually spend their time practising ogam in those coffee shops. In traditional theatre performance, the actor or actress do not use script, so the skill in Ogam is very useful to improvise.